2013
DOI: 10.5194/amt-6-445-2013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between MODIS and AIRS/AMSU satellite-derived surface skin temperatures

Abstract: Abstract. Surface skin temperatures of the Level 3 products of MODIS Collection 5 (C5) and AIRS/AMSU version 5 (V5) have been compared in terms of monthly anomaly trends and climatologies over the globe during the period from September 2002 to August 2011. The MODIS temperatures in the 50° N–50° S region tend to systematically be ~1.7 K colder over land and ~0.5 K warmer over ocean than the AIRS/AMSU temperatures. Over high latitude ocean the MODIS sea surface temperature (SST) values are ~5.5 K warmer than th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The MODIS IST product utilized the MODIS cloud mask with visible reflectance, which had lower accuracy during the night (Hall et al, 2004). Lee et al (2013) reported that the local times of observation between the MODIS and AIRS were almost the same from 60 • N-60 • S, but they were quite different in the high latitude regions. It is likely that the main cause to the observed SST differences near the sea ice boundary was in the way the surface type was classified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MODIS IST product utilized the MODIS cloud mask with visible reflectance, which had lower accuracy during the night (Hall et al, 2004). Lee et al (2013) reported that the local times of observation between the MODIS and AIRS were almost the same from 60 • N-60 • S, but they were quite different in the high latitude regions. It is likely that the main cause to the observed SST differences near the sea ice boundary was in the way the surface type was classified.…”
Section: Discussionmentioning
confidence: 99%
“…The MODIS cloud mask using visible reflectance had a high accuracy during the daytime, but a lower accuracy during the nighttime due to low illumination. As another reason for the temperature difference, Lee et al (2013) suggested that there were substantial differences in observation time between MODIS and AIRS in the high latitude regions, since the different scan angles of the two instruments resulted in different footprints, which could lead to the observed difference in temperature. However, we suggested that the surface type classification method could be the primary reason for the temperature difference between the MODIS-based and AIRS-based data sets.…”
Section: H-j Kang Et Al: Uncertainties Of Satellite-derived Surfacmentioning
confidence: 99%
See 1 more Smart Citation
“…The 95 % confidence intervals for the trends were calculated using the bootstrap method (Wilks, 1995). For each air pollutant anomaly data set, 10 000 new data sets were created to produce 10 000 linear trends through random sampling (e.g., Lee et al, 2013). The random sampling was conducted by drawing data out of the respective original records of the air pollutant anomalies, allowing repetition.…”
Section: Methodsmentioning
confidence: 99%
“…Molnar and Susskind (2005) validated the accuracy of the AIRS/AMSU cloud products using MODIS cloud analyses, which have a higher spatial resolution than that of AIRS. Knuteson et al (2006) compared the MODIS Collection 4 (C4) with the AIRS Version 3 (V3) on the land surface temperature (LST) for the eastern half of the US, showing that the monthly differences were approximately 3 K. Lee et al (2013) investigated the characteristics of the differences between the MODIS land surface skin temperature/sea surface temperature and the AIRS/AMSU surface skin temperature across the globe, and found that the MODIS C5 product was systematically lower by 1.7 K than the AIRS/AMSU V5 product over land in the 50 • N-50 • S regions, but it was higher by 0.5 K than the AIRS/AMSU product over ocean. Particularly in the sea ice regions, the MODIS annual averages were larger than the AIRS/AMSU values, due to the differential errors in ice/snow emissivity between the retrieval methods (or channels) for the two data products.…”
Section: Introductionmentioning
confidence: 99%